A Comparative Analysis on Extrovert and Introvert Students Towards Their Speaking Skill - Agus Rofi’i (ETERNAL (English Teaching Journal), 2017)
This study is an attempt to examine about the extrovert and the introvert students’ speaking skill at the eleventh grade of Senior High School. The samples of this research were 44 students. The design in this research was comparative analysis design. The data were obtained through personality test whether the students are the extrovert or introvert after that the researcher used simulation and role-play technique for testing the students speaking skill. The data were analyzed by using t-test formula to investigate whether there are significant difference result between the extrovert and the introvert students in their speaking skill. The result of the calculation shows that there is no different result between the extrovert and the introvert students in their speaking skill. Groups, the extrovert and the introvert students can perform better English speaking skill through their own way of learning. Hopefully this research can be useful for achieving more effective English teaching and learning process.